Natural magnetite characterization from beach sand prepared by using planetary ball milling. Issue 1 (February 2021) - Jalil, Zulkarnain; Novita Sari, Eva; Ismail, Ismail; Muhammad; Nizar Machmud, M.; Handoko, Erfan
Abstract: In this paper, the mineral composition and magnetic behavior of nano magnetite (Fe3 O4 ) extracted from beach were studied. The beach sand was collected from the Gampong Dayah coastal area, Banda Aceh and prepared by mechanical alloying method. The mineral compositions were investigated by XRD and XRF analysis tests. The XRF test showed that the sand mostly contain Fe3 O4 in association with other isomorphous impurities, such as SiO2, TiO2, Al2 O3 and some others minor minerals in varying proportions. Compare to XRD results, it was consistent with XRF, the phase compositions are mainly magnetite (Fe3 O4 ). The XRD revealed that magnetite is the major mineral components in the Syiah Kuala sand. The electron microscope (SEM) identification showed the fine crystalline structure and the main morphology was micro-crystalline or agglomerate forms. The magnetic properties of the samples after milling showed there has been increasing in coercivity (Hc) and remanent (Br), while magnetic saturation (Ms) was decreased.